2010
DOI: 10.1177/010740831003000108
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Psychological Distress at Home following Elective Surgery in a Representative Group of Surgical Patients: An Explorative Panel Study

Abstract: Background. Physical care and the provision of harmless treatment is the main objective of peri-operative nursing care with psychological distress being less addressed. Aim. The aim of the study is to describe postoperative psychological distress of elective surgical patients and identify factors that are present or known during hospitalisation and detect their associations with the psychological distress at home at least four weeks post discharge from the hospital. Method. 390 patients participated in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…as measured with HADS, both at hospital and up to 6 months postdischarge. In addition, our findings confirm earlier findings that having symptoms of anxiety or depression predicts symptoms of anxiety and depression (Sveinsdóttir, 2010;Sveinsdóttir & Ingadóttir, 2012;Sveinsdóttir & Skúladóttir, 2012), indicating that psychological care is of utmost importance.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…as measured with HADS, both at hospital and up to 6 months postdischarge. In addition, our findings confirm earlier findings that having symptoms of anxiety or depression predicts symptoms of anxiety and depression (Sveinsdóttir, 2010;Sveinsdóttir & Ingadóttir, 2012;Sveinsdóttir & Skúladóttir, 2012), indicating that psychological care is of utmost importance.…”
Section: Discussionsupporting
confidence: 90%
“…Distress caused by postoperative symptoms was the strongest predictor of symptoms of anxiety six weeks postsurgery and symptoms of depression six weeks and 6 months postsurgery. In addition, similar to earlier findings (Sveinsdóttir, 2010; Sveinsdóttir & Ingadóttir, 2012; Sveinsdóttir & Skúladóttir, 2012), more symptoms of anxiety or depression at one time point predict more symptoms at the next time point. A study on depression screening after cardiac surgery found that patients meeting screening criteria for depression at the hospital presented with a higher risk of major adverse cardiac event, depressive mood and having started antidepressants 12 months postdischarge (Tully, Baumeister, Bennets, Rice, & Baker, 2016).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Increased levels of distress-related hormones can affect the cardiovascular system and worsen the prognosis of the patients. 10 In addition, distress has been associated with fatigue level, 11 increased risk of rehospitalization, 12 higher mortality rate, 7,13,14 and poor cardiac prognosis. 15,16 Thus, distress can potentiate the complications of heart disease.…”
Section: Introductionmentioning
confidence: 99%